PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN MEDIASI KOMITMEN ORGANISASI DAN KECUKUPAN ANGGARAN (Studi Empiris pada Satuan Kerja di Wilayah Pembayaran Kantor Pelayanan Perbendaharaan Negara Solok) - Setyawan, Ariyanto; Rohman, Abdul (Diponegoro Journal of Accounting, 2013)
This study is a replication of the previous study by Nouri and Parker (1998), but implemented in the public sector. This study aimed to examine the effect of budgetary participation on managerial performance in public sector organizations / government agencies in the payment areas of KPPN (State Treasury Office) Solok, West Sumatra, in order to obtain results from different institutions (inter-ministerial). This study also aimed to test whether organizational commitment and budget adequacy can serve as mediating the relationship between budgetary participation and managerial performance.The research data is the primary data obtained through questionnaires given to 128 structural units in several government agencies. A total of 43 questionnaires were returned and 31 questionnaires filled out completely and can be processed. Data were processed using path analysis and SmartPLS ver 2.0. with six hypotheses to test the direct and indirect effects of budget participation on performance managerial. PLS were used to predict the relationship between variables. The test results support three hypotheses and reject the other three hypotheses.The results of this study showed a direct effect of budgetary participation on managerial performance. Budgetary participation also significantly affect the budget adequacy and budget adequacy have positive effect on organizational commitment. However, organizational commitment and adequacy of the budget is not proven to act as an intervening variable. This research suggests the public sector organizations / government for budgetary participation can be applied well because it can improve performance and provide sufficient budget to keep the loyalty / commitment of employees.